If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 5) + -1(x + -3) = 40 Reorder the terms: 4(5 + x) + -1(x + -3) = 40 (5 * 4 + x * 4) + -1(x + -3) = 40 (20 + 4x) + -1(x + -3) = 40 Reorder the terms: 20 + 4x + -1(-3 + x) = 40 20 + 4x + (-3 * -1 + x * -1) = 40 20 + 4x + (3 + -1x) = 40 Reorder the terms: 20 + 3 + 4x + -1x = 40 Combine like terms: 20 + 3 = 23 23 + 4x + -1x = 40 Combine like terms: 4x + -1x = 3x 23 + 3x = 40 Solving 23 + 3x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 3x = 40 + -23 Combine like terms: 23 + -23 = 0 0 + 3x = 40 + -23 3x = 40 + -23 Combine like terms: 40 + -23 = 17 3x = 17 Divide each side by '3'. x = 5.666666667 Simplifying x = 5.666666667
| 1m-50=10m+2 | | 3.5-2=1.5 | | 2c+13=4c | | x^3-4x^2+2x=-2 | | 7r^2+24-8=8 | | 9z-8=3 | | 2x+3(4x-10)=96 | | (3x+8)+(5x+12)=180 | | 1-15x=x+36 | | -6(-7-7r)=126 | | x^3-4x^2+2x+2=0 | | 5/2x+11=(5/2)x+11 | | 11x^3-6x^2+x+3=0 | | 4(x+5)+(x-3)=40 | | 3.7*4.8= | | -3m+16=8 | | -(1-m)=-(4m+1) | | X^4-7x^3-2x^2= | | 30z=80+22z | | c+4=-3b-ac | | 5(j+4)+j=-8 | | 10y-96+3x=360 | | 7x+3(2x+11)=111 | | -4x-20=16 | | 2(f+3)-2=8+24 | | 4x+20+2x-14=0 | | 12-4x=2(6-2x) | | 4.8*3.7= | | -(8-m)=-(5m+8) | | 119=4x+3(5x+8) | | 5y-20=40 | | 2ab*4b^3= |